Bidirectional Power Flow Control Integrated With Pulse and Sinusoidal-Ripple-Current Charging Strategies for Three-Phase Grid-Tied Converters - Tang, Cheng-Yu; Chen, Pon-Tzu; Jheng, Jia-He (IEEE access, 2021)
The objective of this paper is to propose bidirectional charging/discharging strategies for three-phase grid-tied converters. The bidirectional power flow control feature of the converter is able to realize both charging and discharging capability. Besides, in order to achieve high charging efficiency as well as extend the life of the battery, five charging strategies are adopted and developed: 1) the constant current (CC) charging, 2) the pulse-ripple-current (PRC) charging, 3) the sinusoidal-ripple-current (SRC) charging, 4) the bidirectional pulse-ripple-current (BPRC) charging and 5) the bidirectional sinusoidal-ripple-current (BSRC) charging. The direct quadrature (d-q) transformation is utilized for the converter to realize different charging methods. These methods can be achieved by the digital signal processor (DSP) without adding extra circuit components. In addition, the charging power differences between each strategy are considered and analyzed in this paper. Finally, both simulation and experimental results obtained from a 5-kW prototype circuit verify the performance and feasibility of the proposed bidirectional charger.